Intercropping of canola and mustard with wheat for higher profitability - Tripathi, Subhash Chandra; Gill, Subhash Chander; Meena, Raj Pal (Journal of Cereal Research, 2016)
A field experiment was conducted during winter seasons of three years from 2010-2011 to 2012-2013 to assess the productivity and profitability of canola and mustard intercropping with wheat in different ratios. Pooled analysis of data recorded over three years revealed that the significantly highest wheat equivalent yield (69.88 q/ha) was recorded in wheat : canola intercropping system in 6:2 ratio followed by wheat : mustard intercropping system (62.33 q/ha) in same ratio. Wheat equivalent yield increase in wheat+canola in 6:2 ratio was to the tone of 47.9 % than yield obtained from sole wheat. heat+canola and wheat+mustard intercropping in 6:2 ratio exhibited 1.61 and 1.53 land equivalent ratio (LER), respectively which was higher than the values recorded in other intercropping systems. The highest gross return (Rs 97833/ ha), net return (Rs 46133/ ha) and B: C ratio (1.89) was obtained under wheat +canola in 6: 2 ratio followed by wheat + mustard in same ratio.